2022
DOI: 10.1002/dev.22277
|View full text |Cite
|
Sign up to set email alerts
|

Parent and child self‐ and co‐regulation during pediatric venipuncture: Exploring heart rate variability and the effects of a mindfulness intervention

Abstract: Needle procedures are common throughout childhood and often elicit distress in children and parents. Heart rate variability (HRV), as an index of emotion regulation, can inform both self‐regulatory and co‐regulatory processes. Mindfulness may serve to regulate distress; however, no research has studied mindfulness or parent and child regulatory responding concurrently during venipuncture. Stemming from a randomized controlled trial investigating a mindfulness intervention, this study sought to describe regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…This study falls under a single-site, two-arm, parallel-group RCT (#NCT03941717) and data collected as part of this larger study are presented in three other manuscripts examining: (1) how a brief mindfulness intervention affected child and parent venipuncture experiences [ 22 ]; (2) whether parent and child HRV differed as a function of venipuncture phase and by RCT group [ 20 ] and (3) biopsychosocial aspects of children’s venipuncture experience [ 23 ]. This paper explores a unique set of research aims related to parent baseline HRV, self-reported states, and child behavior to understand parent behaviors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study falls under a single-site, two-arm, parallel-group RCT (#NCT03941717) and data collected as part of this larger study are presented in three other manuscripts examining: (1) how a brief mindfulness intervention affected child and parent venipuncture experiences [ 22 ]; (2) whether parent and child HRV differed as a function of venipuncture phase and by RCT group [ 20 ] and (3) biopsychosocial aspects of children’s venipuncture experience [ 23 ]. This paper explores a unique set of research aims related to parent baseline HRV, self-reported states, and child behavior to understand parent behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…High baseline HRV is indicative of greater flexibility in emotional responding [ 15 , 16 ]. Existing research on parental baseline HRV in the context of child acute pain are laboratory-based studies demonstrating HRV informs parent behaviors [ 17 , 18 , 19 ] (see [ 20 , 21 ] for parent–child HRV in a clinical context).…”
Section: Introductionmentioning
confidence: 99%